Optimization of a spectrofluorimetric method based on a central composite design for the determination of potassium losartan in pharmaceutical products - Fatma Demirkaya-Miloglu; Mehmet Emrah Yaman; Yucel Kadioglu (Universidade de São Paulo, 2014)
Here, a spectrofluorimetric method for the determination of potassium losartan (PL) in pharmaceutical products is described. The effects of critical parameters, pH, acid molarity, and temperature, on the fluorescence intensity of PL were analyzed, and these parameters were optimized using a central composite design (CCD). The highest fluorescent intensity at excitation (λex) and emission (λem) wavelengths of 248 nm and 410 nm, respectively, was achieved using 0.01 M sulfurous acid (pH 2) at 21.6 °C. Under optimum conditions, the method was linear from 0.025-0.5 µg/mL, with a reasonably high correlation coefficient (0.9993). Furthermore, the method was very sensitive (LOQ, 0.006), accurate (RE, ≤7.06), and precise (%RSD, ≤6.51). After development and validation of the method, samples containing PL were analyzed with this method, and the obtained data were statistically compared with those obtained with a previously published reference method using a two one-sided equivalence test (TOST). According to the data, the results from the proposed and reference assays were equivalent.